Herpes simplex factors: literature review - Begazo-Morán, Lisette (2022)
Herpes simplex virus, after the first infection, can remain dormant in the lymph nodes and reactivate at any time due to certain factors and/or stimuli causing effects in the patient. The purpose of this literature review is to update scientific information on the factors that predispose to the reactivation of herpes simplex virus. A comprehensive literature review was conducted in the LILACS, Scielo, PUBMED, Scopus and the following keywords were used: herpes simplex, reactivation, latency and risks. A factor is reactivation by immunosuppression due to the intake of immunosuppressants or oncological therapy. Another factor is psychological stress, in which the hormones released act on mediating signs of reactivation. Sun exposure that reactivates the virus in infected neurons and infection in pregnant women can trigger complications in the fetus and delivery.